Optimization of Drilling-Fluid Lost-Circulation Control in the Mesozoic Yanchang Formation of Zhengning Oilfield - Peng, Fangquan (International Journal of Natural Resources and Environmental Studies, 2026)
Lost circulation is a major engineering problem that restricts the safe and efficient drilling of oil and gas wells. Reservoirs of the Mesozoic Yanchang Formation in Zhengning Oilfield are generally characterized by low porosity, low permeability, strong heterogeneity, and seepage jointly controlled by fractures and microfractures, which makes the types of lost-circulation channels encountered during drilling highly complex and the plugging operation difficult. On the basis of reviewing the research status of commonly used lost-circulation materials and plugging technologies, this paper combines the reservoir characteristics and lost-circulation background of the Yanchang Formation in Zhengning Oilfield to analyze the block adaptability of existing plugging systems. Drawing on previous studies on lost-circulation optimization in the Yanchang Formation—especially the findings related to particle-size analysis, D90 adaptability evaluation, rheology and filtration tests, and composite-formulation optimization—Chapter 4 is rewritten as an experimental evaluation and optimization of lost-circulation materials. The study shows that lost-circulation control in the Yanchang Formation of Zhengning Oilfield should emphasize a multi-stage synergistic concept of "coarse-particle bridging–medium-particle filling–fine-particle compaction." A broad particle-size-distribution composite system should be preferentially adopted so that the pressure-bearing and anti-erosion capacity of the sealing layer can be ensured while maintaining stable drilling-fluid rheology and filtration performance.